STAKEHOLDERS’ ATTITUDE TOWARD ECOTOURISM DEVELOPMENT IN RINJANI-LOMBOK GEOPARK: THE EVIDENCE FROM MOUNT RINJANI NATIONAL PARK - Shine Pintor Siolemba Patiro; Kresno Agus Hendarto; Hendrian Hendrian; Hety Budiyanti; Rubangi Al-Hasan; Yumantoko Yumantoko; Ahmad Nur; Edi Kurniawan; Naning Yuniarti; Desmiwati Desmiwati; Tri Astuti Wisudayati; Deddy Dwi Nur Cahyono; Yudha Satria Aji Pratama; Yosephine Martha Maria Anita Nugraheni; Tri Dasta Nursehaneka Yatma (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
Based on stakeholder and social exchange theory, this study examined a model of the relationship between stakeholder awareness, perception of impact (environmental, economic, and socio-cultural), and attitude toward ecotourism development in Mount Rinjani National Park (MRNP). The model was tested using a sample of 157 stakeholders. Data were collected by surveying and analyzing using the partial least squares. The results showed that only perception of the economic impacts of ecotourism partially mediated the relationship between awareness and attitude toward ecotourism development. From the perspective of stakeholder theory, the perceived impacts are heterogeneous. These differences will determine their attitude toward the level of support and participation. From the perspective of social exchange theory, the study showed that attitude toward ecotourism development is directly influenced by awareness of ecotourism and the perception of economic impact. The stakeholders on MRNT have a more compromising attitude toward ecotourism development to the socio-cultural and environmental impacts.